2009
DOI: 10.3354/meps07717
|View full text |Cite
|
Sign up to set email alerts
|

Movements, at-sea distribution and behaviour of a tropical pelagic seabird: the wedge-tailed shearwater in the western Indian Ocean

Abstract: This is the first study using geolocators (global location sensing, GLS) to track the movements of a pelagic tropical seabird. We used GLS to describe at-sea distribution and activity patterns of wedge-tailed shearwaters Puffinus pacificus breeding on Aride Island, Seychelles, in the late chick-rearing, non-breeding and pre-breeding periods. During late chick-rearing and pre-breeding periods, shearwaters foraged relatively close to the colony. In the non-breeding period, shearwaters were found on a west -east … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 34 publications
6
60
1
Order By: Relevance
“…Large numbers of nonbreeding birds are not present at this colony during the breeding season (Clarke and Herrod 2014), suggesting post-breeding dispersal from the colony. Migration is a strategy to cope with seasonal variation (Cohen 1967) and post-breeding movements are undertaken by tropical seabirds, including Barau's Petrels (Pterodroma baraui), Cape Verde Shearwaters (Calonectris edwardsii), and Wedge-tailed Shearwaters (Puffinus pacificus) (Catry et al 2009, González-Solís et al 2009, Pinet et al 2011). Cherel et al (2008 found no difference between the sexes in d 13 C value at any stage of the breeding cycle for Great Frigatebirds at Europa Island.…”
Section: Nonbreeding Season Foraging Ecologymentioning
confidence: 99%
“…Large numbers of nonbreeding birds are not present at this colony during the breeding season (Clarke and Herrod 2014), suggesting post-breeding dispersal from the colony. Migration is a strategy to cope with seasonal variation (Cohen 1967) and post-breeding movements are undertaken by tropical seabirds, including Barau's Petrels (Pterodroma baraui), Cape Verde Shearwaters (Calonectris edwardsii), and Wedge-tailed Shearwaters (Puffinus pacificus) (Catry et al 2009, González-Solís et al 2009, Pinet et al 2011). Cherel et al (2008 found no difference between the sexes in d 13 C value at any stage of the breeding cycle for Great Frigatebirds at Europa Island.…”
Section: Nonbreeding Season Foraging Ecologymentioning
confidence: 99%
“…Although the vast majority of studies on niche partitioning among closely related seabirds (cited above) have been conducted in subantarctic or temperate waters where food is seasonally superabundant, some recent studies of tropical seabirds (see Catry et al 2009, Young et al 2010a have sought to investigate these questions for seabirds foraging in epipelagic tropical waters. In such extreme low-resource environments (Longhurst & Pauly 1987), finding a patch of prey is a rare and unpredictable event (Ashmole 1971, Ballance et al 1997, and interspecific competition may differ compared to temperate or polar marine habitats.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, pelagic seabirds have low movement costs and may undertake extensive trans-equatorial migrations in order to exploit seasonally productive areas (Shaffer et al 2006, GuilfordAs their food resources are patchily distributed, tropical seabirds have evolved specific foraging adaptations that enable them to search large areas efficiently (Ballance & Pitman 1999, Weimerskirch et al 2005a). Many species have distinctive wing morphologies or feed in association with sub-surface predators such as tuna (Scombridae) or dolphins (Delphinidae) that drive prey to the surface (Au & Pitman 1986, Spear & Ainley 1998, Catry et al 2009). For example, in the eastern tropical Pacific, selection for flight proficiency in terns (Sternidae) and petrels (Procellariidae) is associated with their use of less productive waters, reducing competition with larger species such as boobies Sula spp.…”
Section: Introductionmentioning
confidence: 99%